PEMBERDAYAAN ANYAMAN UMBAI UNTUK KEBERLANJUTAN KEARIFAN LOKAL DESA TERUSAN, KAMPAR KIRI HULU - Ridia Wulandari (Pelantar Press, 2025)
Weaving is currently popularly used as a container or place to store food ingredients so that it is considered more environmentally friendly and can reduce the use of plastic waste which is an environmental problem in Indonesia. Usually, weaven craftsmen come from the community, especially the poor to produce plaits. Umbai of plant like a pandan as the main raw material for making woven is a resource in the Terusan Vilage, Kampar Kiri Hulu. weaven products that can be produced by the local community are mats and baskets which are often used for their own use due to the lack of access to product marketing outside the community. Weaving tufts based on local wisdom can be used as a medium to preserve the potential of local resources and create community-based economic empowerment for the sustainability of the webbing.